The Effects of Electron‐Donating Substituents on [Ir(bpy)Cp*Cl]+: Water Oxidation versus Ligand Oxidative Modifications. Issue 4 (5th November 2013) - Zhang, Teng; deKrafft, Kathryn E.; Wang, Jin‐Liang; Wang, Cheng; Lin, Wenbin
Abstract: A series of [Ir(bpy)Cp*Cl]Cl (bpy: 2, 2′‐bipyridine; Cp*: pentamethylcyclopentadienyl) complexes with 4, 4′‐ and 6, 6′‐substituents on the bipyridine ring were synthesized and used for water oxidation both electrochemically and with chemical oxidants. Under electrochemical water‐oxidation reaction (WOR) conditions at pH = 1, blue films were observed to deposit on the electrode surfaces for all of the complexes, without the detection of oxygen. For chemically driven WORs, three oxidants with different overpotentials and electron‐transfer kinetics led to very different behaviors. [Ru(bpy)3 ] 3+ was shown to slowly oxidize the ligands without generating oxygen at pH = 3.7. With NaIO4 as the oxidant at neutral pH, oxygen generation was observed, but ligand oxidation was also seen for the complexes with electron‐donating substituents such as –OMe or –OH groups. With Ce 4+ as the oxidant at pH = 1, a competition between water oxidation and ligand decomposition existed; less ligand decomposition was observed for catalysts that are more active for WOR. These results indicate the intricate nature of molecule water‐oxidation catalysts and their complex behaviors that are highly sensitive to water‐oxidation conditions. Abstract : A series of [Ir(bpy)Cp*Cl]Cl complexes with 4, 4′‐ and 6, 6′‐substituents on the bipyridine ring were examined for water oxidation. These complexes are oxidized electrochemically or with Ru(bpy)3 3+ without producing oxygen, but can generate oxygen with NaIO4 and Ce 4+ as oxidants.